Challenges, Opportunities and Status of E-Governance Implementation in Nepal after Federalism - Verma, Sant Kumar; Bharti, Ajay Kumar (International Journal of Computer Sciences and Engineering, 2019)
Today e-governance becomes an important aspect in most of the developing countries, but most developing countries are still far behind it. Over the last one decade Nepal has seen tremendous political transformation. Nepal government has shown a clear vision on implementation of e-governance by deploying their master plan for e-governance (EGMP) in 2006 but still Nepal is far behind in e-governance development index (EGDI) by UN e-government survey. So, this paper will try to enlighten and appraise the e-governance system of Nepal and significant challenges, opportunities and current status of e-government.